CRE for magic(modular, agile, intensified & continuous) processes - Ranade, Vivek V.; Sharma, Mrityunjay K.; Kulkarni, Amol A. (Chemical Engineering Journal, 2015)
Fine and specialty chemical industry caters to several key applications required for maintaining and enhancing quality of life. Most of these fine and specialty chemicals are still manufactured in stirred tank reactors operated in batch or semi-batch modes. A paradigm shift is necessary to transform these into new age, efficient and continuous processes and plants. In this paper, recent attempts of our group on developing MAGIC (modular, agile, intensified and continuous) devices, processes and plants for fine and specialty chemicals industry are discussed. The focus is on key chemical reaction engineering aspects of developing MAGIC processes. An attempt is made to evolve guidelines for designing MAGIC devices and reactors. The discussion will be useful to researchers as well as to industry practitioners. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Agile; Continuous; CRE; Intensified; Modular

Pinched tube flow reactor: hydrodynamics and suitability for exothermic multiphase reactions - Sharma, Mrityunjay K.; Potdar, Shital B.; Kulkarni, Amol A. (AIChE Journal, 2017)
A novel tubular flow reactor where a straight tube is modified by pinching it periodically at a fixed pitch and at different angles is presented. Pinched tubes (straight tube as well as helical coils) with different pitch and angles between successive pinching are studied. This work reports a detailed hydrodynamic study involving single and two-phase flow. Mixing experiments showed that having an angle of 90° between successive pinchs achieves the shortest mixing length when compared to lower angles. Pressure recovery along with sequence of high and low shear zones and change of flow direction imposed better mixing. Residence time distribution studies showed that higher number of pinch sections decreases the extent of dispersion, yet it deviates from plug flow. The performance is evaluated by carrying a homogeneous and two-phase aromatic nitration and also liquid-liquid extraction. Pinched tube presents an economical option as a flow reactor for conducting exothermic reactions. © 2016 American Institute of Chemical Engineers AIChE J, 2016
Keywords: pinched tube flow reactor; pressure drop; residence time distribution; mass transfer; reactions

Assessing the possibilities of designing a unified multistep continuous flow synthesis platform - Sharma, Mrityunjay K.; Acharya, Roopashri B.; Shukla, Chinmay A.; Kulkarni, Amol A. (Beilstein Journal of Organic Chemistry, 2018)
The multistep flow synthesis of complex molecules has gained momentum over the last few years. A wide range of reaction types and conditions have been integrated seamlessly on a single platform including in-line separation as well as monitoring. Beyond merely getting considered as `flow version' of conventional `one-pot synthesis', multistep flow synthesis has become the next generation tool for creating libraries of new molecules. Here we give a more `engineering' look at the possibility of developing a `unified multistep flow synthesis platform'. A detailed analysis of various scenarios is presented considering 4 different classes of drugs already reported in the literature. The possible complexities that an automated and controlled platform needs to handle are also discussed in detail. Three different design approaches are proposed: (i) one molecule at a time, (ii) many molecules at a time and (iii) cybernetic approach. Each approach would lead to the effortless integration of different synthesis stages and also at different synthesis scales. While one may expect such a platform to operate like a `driverless car' or a `robo chemist' or a `transformer', in reality, such an envisaged system would be much more complex than these examples.
Keywords: automation; continuous flow synthesis; cybernetics; multistep flow synthesis; unified platforms

Modulation of reactivity of singlet radical pair in continuous flow: photo-fries rearrangement - Karjule, Neeta; Sharma, Mrityunjay K.; Nithyanandhan, Jayaraj; Kulkarni, Amol (Journal of Photochemistry and Photobiology A: Chemistry, 2018)
Photo-Fries rearrangement of phenyl benzoate is studied using continuous flow for modulating the reactivity of singlet radical pair by changing the viscosity of the solvent. The effect of flow and proximity of the reactants with the light source on the reactivity of radical pair, formed from singlet excited state was investigated in details. In non-viscous solvent, the results from flow synthesis were comparable to batch reactor. In viscous solvents, selectivity of ortho- and para-isomers (o-/p- isomer) of the product could be controlled by changing viscosity as well as the flow rate. Using flow synthesis, ortho- and para-isomer ratio was obtained as high as 8.45 which are twice as compared to batch experiment with in fraction of residence time.

Multi-step continuous flow synthesis of the cystic fibrosis medicine ivacaftor - Vasudevan, N.; Sharma, Mrityunjay K.; Reddy, D. Srinivasa; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2018)
A continuous flow ozonolysis method combined with a multi-step flow sequence is developed for the synthesis of the drug ivacaftor for the first time. Safe ozonolysis, a continuous flow quadruple reaction to construct a quinolone scaffold, and inline extraction followed by continuous phase separation are the key features of the present work. The feasibility of using a continuous mixed flow reactor, commonly referred to as a continuous stirred tank reactor (CSTR), is also investigated for the relatively slow reaction step. The current integrated multi-step flow synthesis can produce 7.2 g of the drug ivacaftor per day on a laboratory scale, which is sufficient to treat 50 patients per day. The present route can also be used as a general route for the synthesis of other related drugs such as quinolone antibiotics.

Novel flow reactor for handling suspensions: hydrodynamics and performance evaluation - Sharma, Mrityunjay K.; Suru, Aditya; Joshi, Anuj; Kulkarni, Amol A. (Industrial & Engineering Chemistry Research, 2020)
A novel reactor concept that can handle solid particles without any moving components in the reactor is proposed and demonstrated in this work. The proposed reactor is designed by arranging the unique shape cavities in a sequence where inlet and outlets are positioned off-center to each other at specific angles and distance. Detailed flow simulation suggested that cavities with diameter D, having aspect ratio H/D similar to 1.53, outlet (having a diameter of 0.2D) positioned at 0.3D from the center and at 180 degrees with reference to the inlet is suitable for the expected performance. The proposed geometry of the reactor with the optimal geometrical configuration was fabricated and hydrodynamics (viz. pressure drop, mass transfer, and heat transfer, and residence time distribution) were studied. The reactor also offered high mass transfer coefficients and is useful for liquid-liquid reactions and extraction. A variety of solid suspensions (glass particles, activated carbon, starch particles, magnesium hydroxide) were tested over a wide range of flow rates for checking the solid handling capability of the reactor. The neutralization reaction of NaOH (with dissolved a-naphthol) with concentrated HCl that results in almost instantaneous precipitation of a-naphthol from the solution is used as a test reaction for a range of a-naphthol concentrations to change the suspension loading. It is shown that the proposed reactor can handle up to 22% (w/v) solid concentration without any clogging for a longer duration of the operation. However, for sticky solid particles, the same reactor would get clogged at the outlet ports for smaller diameters.